2002
DOI: 10.1176/appi.ajp.159.11.1944
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate and Glutamine Measured With 4.0 T Proton MRS in Never-Treated Patients With Schizophrenia and Healthy Volunteers

Abstract: Higher than normal glutamine levels in the left anterior cingulate and thalamus provide in vivo evidence of greater than normal glutamatergic activity proposed by glutamatergic models of schizophrenia. In contrast to other studies in chronically ill patients, no differences were seen in the levels of N-acetylaspartate in either location, suggesting that the findings in patients with chronic schizophrenia may be related to the effect of medication or the progression of the illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
299
5
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(342 citation statements)
references
References 11 publications
33
299
5
5
Order By: Relevance
“…Consequently, thalamic filter function is impaired. If glutamatergic NMDA receptors are dysfunctional in schizophrenia, the present and other studies suggest that secondary disturbances in glial-neuronal interactions and the glutamine-glutamate cycle may occur in this disorder (Do et al, 2000;Theberge et al, 2002Theberge et al, , 2003. This may then contribute to imbalance of the cortico-striato-thalamocortical feedback as also suggested by Laruelle et al (2003).…”
Section: Dopamine and Its Interaction With Glutamate Metabolismsupporting
confidence: 71%
See 1 more Smart Citation
“…Consequently, thalamic filter function is impaired. If glutamatergic NMDA receptors are dysfunctional in schizophrenia, the present and other studies suggest that secondary disturbances in glial-neuronal interactions and the glutamine-glutamate cycle may occur in this disorder (Do et al, 2000;Theberge et al, 2002Theberge et al, , 2003. This may then contribute to imbalance of the cortico-striato-thalamocortical feedback as also suggested by Laruelle et al (2003).…”
Section: Dopamine and Its Interaction With Glutamate Metabolismsupporting
confidence: 71%
“…As pointed out in the Introduction, glutamate and glutamine are very closely linked metabolically. In an in vivo 1 H NMRS study it was suggested that the glutamine signal in spectra of anterior cingulate and thalamus of drugnaive first episode schizophrenia patients was increased compared to age-matched healthy controls (Theberge et al, 2002). However, using 1 H NMRS at low field strength it is not possible to fully separate glutamate and glutamine signals, whereas there is no overlap between these two amino-acid signals using high field 1 H NMRS or HPLC.…”
Section: Glutamate-glutamine-gaba Cycle and Glial-neuronal Interactionsmentioning
confidence: 99%
“…An antagonism at this location could, in turn, cause regional hypermetabolism from increased glutamate release (Gluck et al, 2002;Theberge et al, 2002;Bartha et al, 1997;Moghaddam et al, 1997;Moghaddam and Adams, 1998). The mechanism for this phenomenon may be attributed to disinhibition of inhibitory interneurons in the anterior thalamus, basal forebrain, or frontal cortex (Farber, 2003;Carter et al, 2004;Tomitaka et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Complementary with that finding is a study at 3 T that showed elevated glutamate/glutamine in adolescents who were at high risk for schizophrenia (69). In a more recent study, the same group at a magnetic field strength of 4 T reported that the increase is, in fact, glutamine, without a concomitant change in glutamate (70). Little else has been reported for glutamate, glutamine and GABA in schizophrenia with MRS. At 4 T, the spectral resolution is adequate to differentiate the glutamate and glutamine, but a cautionary note is that, at the 20 ms echo delay used in this study, macromolecules are a significant contaminant of the glutamate and glutamine peaks.…”
Section: Glutamate Glutamine and Gabamentioning
confidence: 87%